Compact planar wearable ultra wideband antenna for on-body applications - Mohammed Al-Ashwal, Wadhah Abdo (2015)
The increasing growth in using body area networks (BANs), wireless personal area networks (WPANs), and medical sensors has given an interest in wearable antennas that are made for operation on the living bodies. Engineers have not stopped at creating a remarkable technology such as wearable systems, but also involved in understanding the interaction of electromagnetic (EM) waves with the body. Studying the interaction between EM waves and the body requires modeling of the body with physical phantoms or with numerical phantoms embedded in numerical electromagnetic codes. In this project, two ultra-wideband (UWB) planar monopole antennas have been reported in this thesis. The substrates of the proposed antennas have been made of jeans while radiators were made of copper tapes. Simulated and measured performances of the antennas in terms of return loss and radiation patterns have been discussed in this work. Recorded results have shown that the operating frequency ranges from 3.04 GHz to 10.3 GHz and from 3.04 GHz to 11.3 GHz with respect to -10 dB for the first and second antennas respectively. The antennas have been tested under severe conditions such as operating in water and aggregates, and results have been presented and discussed. Moreover, an extended study on the safety concerns of the antennas by means of specific absorption rate (SAR) has been included in this work. The approximated SAR has been found to be within the safety guidelines set by Federal Communications Commission (FCC).